2020
DOI: 10.1590/0102-311x00170019
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives for leprosy control and elimination

Abstract: Recently, data and news about rising numbers of leprosy cases in some low endemic countries, as well as in certain areas of high-burden countries, have become prominent 1 . This increase leads us to reflect upon changes in transmission patterns and difficulties regarding interventions strategies for leprosy control.Leprosy is classified as a neglected tropical disease (NTD) targeted for elimination 2 . The goal of elimination as a public health problem was agreed upon by the Member States of the World Health O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
0
7
0
4
Order By: Relevance
“…At the same time, PB mainly presents cellular immunity, which is not easily assessed through either POC immunochromatographic or immunoassays. 49 Identifying a host biomarker signature to support diagnosis has made a significant advance, with high titters of anti-PGL-1 IgM, IP-10/CXCL-10 and CRP being associated with leprosy. 50…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, PB mainly presents cellular immunity, which is not easily assessed through either POC immunochromatographic or immunoassays. 49 Identifying a host biomarker signature to support diagnosis has made a significant advance, with high titters of anti-PGL-1 IgM, IP-10/CXCL-10 and CRP being associated with leprosy. 50…”
Section: Discussionmentioning
confidence: 99%
“…The WHO recommends SDR-PEP, and some national programs have already included or are considering to include such interventions in the routines of their health services. It is also important to create partnerships with other institutions in order to develop new and more effective tools and initiatives for the prevention and control of leprosy [ 12 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the long incubation period and the slow clinical progression of leprosy [ 12 ], it is reasonable to consider systematic leprosy screening for all CL patients seeking assistance in health facilities [ 5 ]. In fact, most patients who presented both diseases during our study period were first diagnosed with CL; within three years, most of them were diagnosed with the second disease.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our findings also suggested that adult individuals are more likely to present a second disease. In addition to a greater exposure to CL vectors [ 46 ], this increased risk may be attributed to the higher number of interpersonal contacts and the long incubation period of leprosy [ 12 , 44 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation